Поэзия Николая Тихонова в армянских переводах - Р. А. Багдасарян (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Նիկոլայ Տիխոնովի պոեզիայի նմուշները տարբեր տարիներին գրավել են հայ բանաստեղծների և թարգմանիչների ուշադրությունը։ The samples of Nikolay Tlkhonov's poetry attracted the attention of Armenian poets and translators in different years.
Keywords: Literature; Language and Literature; Translation and interpretation